ANALISIS LAPORAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH PADA DINAS PEKERJAAN UMUM KABUPATEN MINAHASA - Worotikan, Jenefer Hermina; Sondakh, Jullie J.; Gamaliel, Hendrik (Universitas Sam Ratulangi, 2018)
Department of public work of Minahasa district is one of the agencies within the scope of governmental of Minahasa district which has responsibility to compose accountabilities Performance peport of Government instance. LAKIP is a form of the government accountability onÂ performance implementation which is carried out within a year estimates and as on of the manifestation of good governance. The purpose of this study was to analyze what factors caused the format of LAKIP formulation to the DPU not to fulfill the suitability of the elements of the formatting format in accordance with the Regulation of the Minister of State for Administrative Reform and Bureaucratic Reform number 29 year 2010 consisting of executive summary, introduction, planning and agreement performance, performance accountability, strategic plan, annual performance plan form (CTR), key performance indicators (IKU), performance agreement form, closing, attachments. The elements that are not yet in accordance with the regulations are the main performance indicators, covers and attachments. The methods of data collection which is used are interviews and documentation. The method of analyses of data which used is descriptive qualitative. The results of this study indicate that the format of the 2016 Minahasa DPU LAKIP drafting has largely compiled in accordance with PERMENPAN number 29 year 2010 but there are still elements in the format of the DPU LAKIP preparation that are not in accordance with the regulation.Keywords : LAKIP, good governance, accountability.